Біфуркація розв'язків крайової задачі для систем інтегро-диференціальних рівнянь з виродженим ядром - Бондар, І.А.; Овчар, Р.Ф. (Нелінійні коливання, 2017)
Найдены достаточные условия существования решений слабовозмущенной линейной краевой задачи для системы интегро-дифференциальных уравнений. Установлены условия существования и единственности решений таких задач. Предложен итерационный процесс построения решения. We find sufficient conditions for existence of solutions to a weakly perturbed boundary-value problem for a system of integro-differential equations. We establish existence and uniqueness of solutions to such problems. We also give an iteration procedure for solution construction.